The Representation of Social Actors in Political Editorial Reports of an On-Line Indonesian National Newspapers - Barzan Faizin (UIN Sunan Gunung Djati, 2022)
This article is a critical discourse analysis of the representation of social actors in an on-line Indonesian National newspaper’s (Media Indonesia) editorial reports on the political issues on ‘intolerance’ recovery, the allocation of Regional Government Budget, and reclamation project post the Jakarta governor election 2017. In line with this historical event, this study attempts to examine how social actors—Anies, Ahok and society are represented in the MI’s editorial reports. The main objectives of this research are: (1) to examine the exclusin and inclusion strategies in which the social actors are represented in the reports, and (2) to describe how the social actors are positioned (whether) in the positive self- and negative other presentation This study applied Van Leeuwen’s Social Actor Network and Wodak’s Discourse-Historical Approach. The study reveals that the present governor, Anies is mostly represented negatively in the political issues post the Jakarta governor election 2017. Conversely, the other social actor, Ahok is completely portrayed in a positive manner and society is depicted in a neutral mode. In the terms of power and ideology, it is obvious that Media Indonesia has a dominant power over its readers, and embraces secularism ideology in politics and capitalism ideology in economy.